From Arabian tribes to Islamic Empire: army, state and society in the Near East c. 600 - 850 - Crone, Patricia (Variorum collected studies series, 2008)
Introduction -- The Arabian background -- The tribe and the state -- Tribes and states in the Middle East -- The first-century concept of hiǧra -- The later evolution -- Were the Qays and Yemen of the Umayyad period political parties? -- A note on Muqātil b. Ḥayyan and Muqātil b. Sulaymān -- The significance of wooden weapons in al-Mukhtār's revolt and the ʻAbbāsid revolution -- On the meaning of the ʻAbbāsid call to al-Riḍā -- The ʻAbbāsid Abnāʼ and Sāsānid cavalrymen -- The early Islamic world -- The pay of client soldiers in the Umayyad period -- Mawālī and the prophet's family : an early Shīʻite view -- Imperial trauma : the case of the Arabs